Navigating climate change: Climate change awareness and strategies in micro, small, and medium-sized enterprises in a developing economy - Julián Andrés Díaz Tautiva; Sebastian Barros-Celume; Antonio Lecuna; Camila Barragan-Rodriguez (PLoS ONE, 2025)
Given the limited research on climate change (CC) awareness and strategies among micro, small, and medium-sized enterprises (MSMEs), this study aims to address three key questions: To what extent are MSMEs aware of CC and decarbonization? How do MSMEs strategize to address CC and achieve carbon neutrality? What factors shape MSMEs’ attention to CC and decarbonization? Drawing on theoretical insights from the Attention-Based View, we analyze CC awareness and strategies among 1,453 Colombian ventures to identify common patterns and traits between them. Our findings reveal a significant gap in MSMEs’ understanding of essential concepts such as carbon neutrality, decarbonization, and the overall impacts of CC on their businesses. Moreover, the results indicate that most MSMEs exhibit greater awareness of CC-related strategies at the corporate practice level than those aimed at operational processes. On average, respondents estimate that achieving carbon-neutral emissions will take between five to twenty years. Based on our findings, we propose scholarly, managerial, and policy recommendations to enhance CC awareness and promote effective CC-related strategies across MSMEs from different economic sectors.